(untitled) (Vietnam Journal of Community Medicine, 2022)
Objective: To determine the prevalence of foreskin stenosis in preschool children in Quang Xuong District, Thanh Hoa Province. Subjects and methods: All pre-school boys ages 19 to 72 months at the kindergarten of Quang Xuong Thanh Hoa. Study design is cross-sectional study without control group: Age, characteristics of the foreskin, inflammation of the glans, and condition of the glans mucosa are inclucded in the clinical description. Results: Mean age is 50.17±12.58 months, paraphimosis is accounted for: 62.91%; phimosis is 28.73%, and penis subsidence is 2.18%. The condition of the glans mucosa: No adhesion of the glans mucosa 12 %; adherence is seen in 59.27%; There are 28.73% mucosal status due to phimosis has not been identified. The average penis length in the group of children with phimosis is 2.68±0.77cm; paraphimosis is 2.68±0.59cm; penis subsidence: penis average length 0.75±0.27cm; There is a difference in mean penis length between groups with p<0.05.